2016
DOI: 10.1097/jpo.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Development and Real World Use of a Vibratory Haptic Feedback System for Upper-Limb Prosthetic Users

Abstract: Introduction Sensory feedback is largely unavailable for persons with upper-limb amputation with conventional prostheses. The current study created a portable vibratory haptic feedback system integrated into the prosthesis to test its usefulness in gripping objects during daily life. Materials and Methods Development involved optimizing a mapping algorithm between the force sensor and the feedback tactor vibration, developing a custom process for mounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…In an attempt to address these issues, researchers have developed low-cost wearable feedback systems. In the case of transradial amputations, systems have been developed to provide vibrational feedback against the skin in response to forces measured on the terminal device [22] [24] . Tactors have been placed proximal to the prosthetic socket; in two studies the tactor was placed underneath the prosthetic liner [23] , [24] and in one it was secured within an elastic cuff [22] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to address these issues, researchers have developed low-cost wearable feedback systems. In the case of transradial amputations, systems have been developed to provide vibrational feedback against the skin in response to forces measured on the terminal device [22] [24] . Tactors have been placed proximal to the prosthetic socket; in two studies the tactor was placed underneath the prosthetic liner [23] , [24] and in one it was secured within an elastic cuff [22] .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of transradial amputations, systems have been developed to provide vibrational feedback against the skin in response to forces measured on the terminal device [22] [24] . Tactors have been placed proximal to the prosthetic socket; in two studies the tactor was placed underneath the prosthetic liner [23] , [24] and in one it was secured within an elastic cuff [22] . These studies have demonstrated potential for reducing grasp force [24] , improving performance [22] , and improving grip force accuracy at low force levels [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Markovic et al showed that there was no significant advantage with a vibrotactile bracelet in a box and blocks task [18]. Vibrotactile feedback was also shown not to have a significant effect on grip force accuracy at medium and high grip forces [19]. Given the mixed results on the benefits of haptic feedback for myoelectric prostheses, it becomes clear why haptic feedback of any modality has remained largely absent from commercial prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…When trying to control the force applied by the prosthetic hand, haptic feedback is helpful to reconnect this severed sensation of touch for the amputee, to give an indication about the applied force and enhance the grip force control. [24][25][26] Many noninvasive interfaces used by different research groups have been proposed for haptic feedback to restore the haptic experience, including vibrotactile stimulation, [27][28][29] electrotactile stimulation, [30][31][32][33] and mechanotactile feedback. [34][35][36] Passively powered pneumatic actuators have also been previously used to map the robotic fingertip forces to the residual limb of amputees, 36 A soft robotic armband with pump-driven pneumatic chambers for haptic feedback has also been designed in the past, which was previously tested with 10 human subjects who were able to recognize six discrete air pressure levels (10-35 kPa with 5 kPa increments) corresponding to six levels of robotic fingertip force.…”
Section: Introductionmentioning
confidence: 99%